In vitro and in vivo assessment of phage therapy against Staphylococcus aureus causing bovine mastitis. (September 2020) - Ngassam-Tchamba, C.; Duprez, J.N.; Fergestad, M.; De Visscher, A.; L'Abee-Lund, T.; De Vliegher, S.; Wasteson, Y.; Touzain, F.; Blanchard, Y.; Lavigne, R.; Chanishvili, N.; Cassart, D.; et al.
Highlights: Lytic activities of three bacteriophages in vitro against bovine mastitis Staphylococcus aureus . Survival rate below 50% in vivo at DPI 4 with Galleria mellonella larvae. Incomplete recovery of the mouse mastitis in vivo at HPI 48. Significant differences after blending of larvae and mice mammary glands. Abstract: Objective: The aim of this study was to assess the efficacy of lytic bacteriophages on Staphylococcus aureus causing bovine mastitis, by in vitro and in vivo assays using Galleria mellonella and murine mastitis models. Methods: Between May and December 2016, ten S. aureus (five methicillin-resistant and five methicillin-sensitive) isolates were isolated from milk samples of cattle with mastitis in Belgium and Norway. The isolates were assessed in vitro for their susceptibility to four lytic bacteriophages (Romulus, Remus, ISP and DSM105264) and subsequently in vivo in G. mellonella larvae and in murine mastitis model. Results: Romulus, Remus and ISP showed a lytic activity against the S. aureus isolates in vitro. A larvae survival rate below 50% was observed at 4 days post-inoculation (DPI) in the groups infected with a methicillin-sensitive S. aureus isolate and treated with these three phages in vivo. An incomplete recovery of the mouse mastitis was observed at 48 h post-inoculation (HPI) in the groups infected and treated with the ISP phage in vivo. Conclusions: The observations are much more pronounced statistically between the infected- phosphate buffered saline (PBS)-treated and infected-phage-treated groups in G. mellonella and the murine mastitis model demonstrating an effect of the phages against S. aureus associated with bovine mastitis.